Sexual dysfunction in epilepsy: identifying the psychological variables - SOUZA,ELISABETE ABIB P. DE (2000)
In order to evaluate the psychological variables that affect sexual dysfunction (SD) in epilepsy, where compared 60 epileptics (Group 1) with 60 healthy individuals (Group 2), through the State-Trait Anxiety Inventory (Spielberger et al., 1970), Beck Depression Inventory (Beck, 1974) and Sexual Behavior Interview (Souza, 1995). Sexual dysfunction (SD), anxiety and depression were found more frequently in Group 1 than in Group 2 and were not related to sex. Variables such as the onset duration and frequency of seizures as well as the use to medication were not associated with SD. Temporal lobe epilepsy was related to SD (p = 0.035) but not to anxiety or depression. Anxiety and depression were related to SD in both groups. Perception in controlling the seizures was closely related to anxiety (p = 0) and depression (p = 0.009). We conclude that psychological factors play an important role in the alteration of sexual behavior in epileptics and that suitable attention must be given to the control of these variables.